PERAN INOVASI PRODUK MEMEDIASI PENGARUH ORINTASI PASAR TERHADAP KEUNGGULAN BERSAING - Dewi, Putu Ratih Argita; Giantari, I Gusti Ayu Ketut (Buletin Studi Ekonomi, 2021)
The purpose of this study was to explain the role of product innovation in mediating the influence of market orientation on competitive advantage in Silver MSMEs in Celuk Village, Sukawati Gianyar District. This study used a sample of 30 SMEs with the method of determining the sample, namely purposive sampling. The data collected is by distributing questionnaires. The analysis technique used is PLS-based SEM. The results showed that, market orientation has a positive and significant effect on competitive advantage, market orientation has a positive and significant effect on product innovation, product innovation has a positive and significant effect on competitive advantage, and product innovation is able to positively and significantly mediate the effect of market orientation. against competitive advantage. Based on the results of this study, the SMEs of Silver in Celuk Village, Sukawati Gianyar District have carried out market orientation by maintaining customer commitment and have made product innovations, namely routinely adding new product designs.